Le Palais Royal. - Restif de La Bretonne, 1734-1806. (Tufts University. Tisch Library., 2016)
Volume 3 of 3.; 1 online resource (3 volumes) : illustrations.; Pagination: volume 1: 229 pages, 1 unnumbered folding leaf of plates; volume 2: 230 pages, 1 unnumbered folding leaf of plates; volume 3: 229 pages, 1 unnumbered folding leaf of plates.; With half titles.; Illustrations: Folding engraved frontispieces: volume 1: "Les trente deux Filles, dans l'Allée des Soupirs;" volume 2: "Le Cirque;" volume 3: "La Colonnade."; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.